2014
DOI: 10.1353/cch.2014.0010
|View full text |Cite
|
Sign up to set email alerts
|

Hindu City and Just Empire: Banaras and India in Ali Ibrahim Khan's legal imagination

Abstract: This article examines the career and ideas of a late Mughal administrator, a Shi'a Muslim called Ali Ibrahim Khan, who was appointed magistrate of the north Indian city of Banaras after its conquest by the East India Company in 1781, and remained in that position until his death in 1792. Engaging with recent research on legal pluralism on the one hand, and on legal and cultural intermediaries on the other, this paper examines the imagination of imperial, religious and legal spaces by this prolific historian, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In doing so, I have suggested that these petty agents not only "jockeyed" and navigated the conflicting jurisdictions of imperial law, but also thought clearly and rationally about how to reconcile them. 23 The Indian mahzar-namas were recorded testimony documented by expert scribes at the edges of the legal process, and aimed principally but not exclusively at influencing legal outcomes. They were expressed in coded forms that derived from a complex Islamic, Persianate, and Indian heritage.…”
mentioning
confidence: 99%
“…In doing so, I have suggested that these petty agents not only "jockeyed" and navigated the conflicting jurisdictions of imperial law, but also thought clearly and rationally about how to reconcile them. 23 The Indian mahzar-namas were recorded testimony documented by expert scribes at the edges of the legal process, and aimed principally but not exclusively at influencing legal outcomes. They were expressed in coded forms that derived from a complex Islamic, Persianate, and Indian heritage.…”
mentioning
confidence: 99%